2021
DOI: 10.1029/2021jd034550
|View full text |Cite
|
Sign up to set email alerts
|

Future Climatic Projections and Hydrological Responses in the Upper Beijiang River Basin of South China Using Bias‐Corrected RegCM 4.6 Data

Abstract: Global climate change has a significant impact on the water cycle and natural ecosystems. The quantification of the impact of climate change on precipitation, temperature, and water resources has attracted substantial attention (IPCC, 2013). Global climate models (GCMs) have been developed and applied increasingly in recent decades (Stouffer et al., 2017;IPCC, 2013;Taylor et al., 2012). However, the low spatial resolution of GCMs is inadequate for high-precision and high-resolution climate information required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Notably, during the calibration period (2009-2014), the highest daily average flow reached 3350.00 m 3 /s at the source of the Yellow River on 24 July 2012, and 3320.00 m 3 /s at the source of the Yangtze River on 24 July 2009. Employing the 95% quantile [36] of runoff values for the study period as the extreme runoff threshold (as illustrated in Figure 6), it was observed that, in most instances, both reanalysis datasets and observed data tend to underestimate peak flows during runoff simulations at the sources of both the Yellow River and the Yangtze. This discrepancy may arise from the SWAT model's limitation in accurately representing the glacier and soil thawing processes in the SYYR region during the thaw period.…”
Section: Flow Simulation In the Syyrmentioning
confidence: 99%
“…Notably, during the calibration period (2009-2014), the highest daily average flow reached 3350.00 m 3 /s at the source of the Yellow River on 24 July 2012, and 3320.00 m 3 /s at the source of the Yangtze River on 24 July 2009. Employing the 95% quantile [36] of runoff values for the study period as the extreme runoff threshold (as illustrated in Figure 6), it was observed that, in most instances, both reanalysis datasets and observed data tend to underestimate peak flows during runoff simulations at the sources of both the Yellow River and the Yangtze. This discrepancy may arise from the SWAT model's limitation in accurately representing the glacier and soil thawing processes in the SYYR region during the thaw period.…”
Section: Flow Simulation In the Syyrmentioning
confidence: 99%